Wings for Wyatt - Pearl, Alexa, 1967- (Pearl, Alexa, 1967- Tales of Sasha., 2017)
During a visit home, everyone treats Sasha differently except her best friend, Wyatt, so she tries to find a way for him to fly with her to the Island of Royal Flying Horses.